Ultrasound core biopsies of neck lumps: an experience from a tertiary head and neck cancer unit. Issue 9 (16th September 2021) - Adeel, M; Jackson, R; Peachey, T; Beasley, N
Abstract: Background: Traditionally, fine needle aspiration cytology was the primary diagnostic investigation for head and neck lumps; however, ultrasound-guided core biopsy offers the advantage of preserving tissue architecture with increased tissue yield. This study reviews the diagnostic utility of ultrasound-guided core biopsy for investigating head and neck lumps. Methods: Overall, 287 ultrasound-guided core biopsies were reviewed between May 2017 and April 2019 at a single tertiary site for head and neck cancer. Results: On initial ultrasound-guided core biopsy, a diagnostic sample was obtained in 94.4 per cent of patients and in 83.7 per cent of patients with lymphoma. Where the initial ultrasound-guided core biopsy was non-diagnostic, 50 per cent of samples were diagnostic on repeat ultrasound-guided core biopsy. Overall, five complications were seen related to ultrasound-guided core biopsy, and all were managed conservatively. No cases of disease recurrence were identified at the biopsy site. Conclusion: Ultrasound-guided core biopsy is a safe procedure with a high diagnostic yield when investigating head and neck lumps. Patients whose ultrasound-guided core biopsies were non-diagnostic should be considered for excisional biopsy over repeat ultrasound-guided core biopsy.